Biofilms and catheter related bloodstream infection: a tale of two kigdoms - Borges, Vítor (2021)
Background: Biofilm-associated infections are a public health concern in the context of healthcare-associated infections (HAI) such as catheter-related bloodstream infections (CRBSI). Here, we studied two top ten CRBS etiological agents, Enterobacter cloacae and Candida parapsilosis, isolated from a patient with CRBSI in order to understand the role played by biofilms on this HAI. Materials/methods: E.cloacae and C.parapsilosis were isolated from CVC and peripheral blood by standard procedures. EUCAST guidelines were followed for antimicrobial susceptibility evaluation. Single and/or mixed biofilms were assembled on different materials in Mueller-Hinton broth with 2% glucose. Biofilm assembly was assessed by crystal violet assay and scanning electron microscopy (SEM). Fluorescence in situ hybridization (FISH) was used for identification and to assess microorganisms distribution within the biofilm (3D reconstruction). In addition, Focus Ion Beam (FIB)-SEM was used to assess biofilms assembled on inner and outer surfaces of CVCs and construct tomograms. CVC and hemoculture (HC) isolates were subjected to whole-genome sequencing (WGS). Results: All Enterobacter and Candida isolates were antimicrobial resistant. Of note, E. cloacae-CVC revealed an additional resistance (ceftolozame-tazobactam) in comparison to the HC- isolate. Both microorganisms assembled biofilms on glass, polystyrene and polyurethane. Mixed biofilms were denser when both microorganisms were present from the beginning. Biofilm phenotype was not dependent of biofilm initiation by E.cloacae or C.parapsilosis. FISH and SEM analysis showed that biofilm bottom layer was in all cases richer in E.cloacae. Environmental isolates of the same species were also tested, showing that this biofilm phenotype is not a general feature. Using polyurethane catheters (shape/material factor), we observed denser mixed biofilms richer in EPS. FIB-SEM preliminary results suggest that biofilms assembled on inner and outer catheter surface might differ on microorganisms’ distribution. WGS confirmed the genetic identity of the CVC/HC pairs while corroborating the virulence potential and antimicrobial resistant character of the CRBSI-driving pathogens. Conclusions: The results suggest that biofilms allow interaction and adaptation of microorganisms belonging to different kingdoms (Bacteria and Fungi). Adaptation might affect virulence in a transitory or permanent fashion, with potential impact on microorganisms’ potential to cause CRBSI.